Pengaruh Waktu Alkalisasi dan Variasi Arah Terhadap Kekuatan Mekanik Komposit Polyester Serat Agave - Fahru Septiyandi; Rizal Hanifi; Viktor Naubnome (Peneliti.net, 2023)
Natural fiber reinforced composites are influenced by the characteristics of natural fibers, matrix, fiber bonding and fiber treatment. Examples of the treatment are alkalization and direction to determine the effect of the two treatments on the tensile strength produced by the composite material. The alkalization process uses 5%NaOH with immersion time 2 hours, 4 hours and 6 hours and combined with variations vertical, horizontal and random directions with the fraction used 85% 15% hand layup method and ASTM D638-02a standard test. the direction variation the highest tensile strength value produced in the vertical direction with a value of 43.76 MPa 6.67% strain and 6.55 MPa elastic modulus and the lowest value produced in the horizontal direction with tensile value of 2.32 MPa 0.47% strain and elastic modulus 5.05 MPa. While the best soaking time in the horizontal and random directions was 4 hours while for the vertical variation it was 2 hours because it had better fiber density and density than alkalization times 4 and 6. The best alkalization time for agave sisalana fiber based on 2 of the 3 variations in direction was 4 hours , so researchers took the best outline of the alkalization process is 4 hours.